Theorizing digital cultural heritage a critical discourse - Cameron, Fiona 1960-; Kenderdine, Sarah 1966- (MIT Press, 2007)
In Theorizing Digital Cultural Heritage, experts offer a critical and theoretical appraisal of the uses of digital media by cultural heritage institutions. Previous discussions of cultural heritage and digital technology have left the subject largely unmapped in terms of critical theory; the essays in this volume offer this long-missing perspective on the challenges of using digital media in the research, preservation, management, interpretation, and representation of cultural heritage. The contributors - scholars and practitioners from a range of relevant disciplines - ground theory in practice, considering how digital technology might be used to transform institutional cultures, methods, and relationships with audiences. The contributors examine the relationship between material and digital objects in collections of art and indigenous artifacts; the implications of digital technology for knowledge creation, documentation, and the concept of authority; and the possibilities for "virtual cultural heritage" - the preservation and interpretation of cultural and natural heritage through real-time, immersive, and interactive techniques.
Includes bibliographical references and index
Keywords: Art numérique; Biens culturels - Numérisation; Documentation de bibliothèque - Numérisation; Musées - Gestion des collections; Musées virtuels; Cultural property -- Digitization; Digital art; Library materials -- Digitization; Virtual museums; Museums -- Collection management; Digitalisierung; Bibliotheksbestand; Kulturerbe; Museumsbestand; Aufsatzsammlung